Tumor-specific antigens in cutaneous T-cell lymphoma: Expression and sero-reactivity - Eichmüller, Stefan B.; Usener, Dirk; Thiel, Daniela; Schadendorf, Dirk (International journal of cancer, 2003)
Cutaneous T-cell lymphoma (CTCL) is a heterogeneous group of extra-nodal non-Hodgkin lymphomas with primary manifestation in the skin with poor treatment options in the advanced stages. As basis for future immune-therapeutic strategies we have investigated the possible expression of tumor-specific targets in CTCL focusing mainly on so-called cancer-germline genes. cDNAs derived from 20 CTCL tissues and 4 CTCL cell lines were tested with 15 gene-specific and 4 gene family-specific primers by RT-PCR and confirmative Northern blotting. The most frequently detected mRNAs were LAGE-1 (55% with only partial coexpression of the splicing variants), cTAGE-1 (35%), MAGE-A9 (27%) and the GAGE-3-7 group (35%). Furthermore, we could detect NY-ESO-1 (21%) and a MAGE-A subgroup (15%), whereas sub-specification of the latter proved absence of MAGE-A1, -A2, -A3, -A6 and -A12. SCP-1 was found in only one specimen and a several antigens could not been detected in any tumor tissue or cell line (MAGE-B, GAGE-1,2,8 and all 4 RAGE genes). 90% of all CTCL samples were positive for at least 1 of the frequent mRNAs in RT-PCR (LAGE-1, NY-ESO-1, cTAGE-1, MAGE-A9, or GAGE-3to7). Using a secondary SEREX approach we could detect sero-reactivity in sera of CTCL patients against recombinant cTAGE-1 (10/29), GAGE (3/19), MAGE-A1 (1/18), -A3 (1/18), -A6 (2/18) and -A9 (4/18) protein, but not against LAGE-1a, MAGE-A4b or MAGE-A12 protein (n = 19). We conclude, that certain cancer-germline genes can be detected frequently in CTCL and are able to elicit a systemic immune response. These candidate genes might therefore be promising targets for immunotherapeutic interventions in CTCL.